A methodology for the design, fabrication and testing of axially graded polymeric structures with tailored vibration characteristics. (February 2021) - Segura, Mariona Heras; Singh, Kumar; Khan, Fazeel
Abstract: Machinery subject to internal and/or external mechanical excitations typically require careful control or avoidance of undesirable vibration behavior to meet operational constraints. To address this difficulty, the design, fabrication and testing of multi-polymer axially graded (segmented) structures fabricated through 3D printing was performed. Experiments were conducted on axially graded beams composed of four different polymers in a linear spatial arrangement. The ability to combine multiple materials through additive manufacturing affords the ability to create graded structures that can meet specific performance metrics: higher damping at the desired vibration modes and greater modal separation has been successfully demonstrated. The significance of this work is vested in the fact that the proposed technique can enable the development of tuned structures which can deliver desired spectral characteristics. Furthermore, strength, stability (e.g. buckling) as well as vibrational targets in the design of machinery can be met simultaneously using axial grading of materials. Highlights: Vibration performance control using axial grading of polymers. Fused deposition modeling to create graded/segment structures. Scope for novel design of support structures for vibration applications.